CAUSATIVE ANALYSIS OF FOREIGN CAPITAL INFLOW AND ECONOMIC GROWTH IN NIGERIA: A TODA-YAMAMOTO APPROACH - MUHAMMAD , IBRAHIM ABDULLAHI; LAWAL Department of Economics, Bayero University, Kano, KABIRU (JOURNAL OF ECONOMICS AND ALLIED RESEARCH, 2025)
This study explored the causative effect between foreign capital inflows and economic growth in Nigeria, using time series data from 1980 to 2022. Foreign aid, external debt, remittances and Foreign Direct Investment (FDI) were used as proxies for foreign capital inflows, while real Gross Domestic Product (GDP) was used as a measure of economic growth. Data used were sourced from the CBN Statistical Bulletin and World Development Indictors (WDI) database. The variables were first subjected to unit root tests, using Augmented Dickey-Fuller method, to determine the stationary property of the series. The results obtained indicates that some of the variables are integrated at level, while others at first difference; a mixture of I(0) and I(1). Toda-Yamamoto causality test was used to determine the causative direction between foreign capital inflow and economic growth. The results indicated that there is a unidirectional causality running from foreign aid to GDP and from remittances to GDP. The results also revealed no causality between GDP and FDI, and between GDP and external debt. It is therefore recommended that policymakers in Nigeria should ensure a sound macroeconomic policy environment that is stable to stimulate domestic savings, attract additional FDI and utilize external debt effectively. The need for diversification of the economy through industrialization, agriculture, trade and services is also paramount to reduce such substantial dependence on capital from foreign sources